ICSE Board: Suggested Books     ICSE Board:  Foundation Mathematics
Class 8: Reference Books               Class 8: NTSE Preparation
--------------------------------------------------------------------------

Q.1. Find the following products;

  i)    \left(x+5\right)\left(x+7\right)    

     =\ x^2+5x+7x+35     

     ={\ x}^2+12x+35     

    \\     

 ii)  \left(b+2\right)\left(b+9\right)    

    ={\ b}^2+2b+9b+18    

    ={\ b}^2+11b+18    

    \\     

 iii)    \left(c+2\right)\left(c+\frac{3}{5}\right)    

    ={\ c}^2+2c+\frac{3}{5}c+\frac{6}{5}    

    ={\ c}^2+\left(2+\frac{3}{5}\right)c+\frac{6}{5}    

    =\ c^2+\frac{13}{5}c+\frac{6}{5}    

    \\     

  iv)   \left(t+\frac{4}{3}\right)\left(t+\frac{1}{3}\right)    

    ={\ t}^2+\frac{4}{3}t+\frac{1}{3}t+\frac{4}{9}    

    ={\ t}^2+\frac{5}{3}t+\frac{4}{9}    

    \\     

Q.2. Find the following products;

 i)    \left(y+8\right)\left(y-4\right)    

    =\ y^2+8y-4y-32    

    ={\ y}^2+4y-32    

    \\     

  ii)   \left(z+6\right)\left(z-11\right)    

    ={\ z}^2+6z-11z-66    

 = {\ z}^2-5z-66  

    \\     

  iii)   \left(c-5\right)\left(c+1\right)    

    ={\ c}^2-5c+c-5    

    =\ c^2-4c-5    

         \\         

  iv)   \left(b-13\right)\left(b+10\right)    

    ={\ b}^2-13b+10b-130    

=b^2-3b-130

         \\         

Q.3. Find the following products;

    i) \left(x-3\right)\left(x-6\right)    

    ={\ x}^2-3x-6x+18     

    ={\ x}^2-9x+18     

         \\         

    ii) \left(z-11\right)\left(z-4\right)    

    =\ z^2-15z+44     

  = \ z^2-11z-4z+44  

         \\         

    iii) \left(b-6\right)\left(b-8\right)    

    =\ b^2-6b-8b+48     

    ={\ b}^2-14b+48     

         \\         

   iv)  \left(a-\frac{3}{5}\right)\left(a-\frac{1}{3}\right)    

    ={\ a}^2-\frac{3}{5}a-\frac{1}{3}a+\frac{1}{5}     

    = a^2-\frac{14}{15}a+\frac{1}{5}     

         \\         

Q.4. Explain the following;

  i)  \left(x-\frac{1}{2}\right)\left(x+\frac{3}{2}\right)   

    ={\ x}^2-\frac{1}{2}x+\frac{3}{2}x-\frac{3}{4}   

    ={\ x}^2+x-\frac{3}{4}   

         \\         

  ii)  \left(p-3\right)\left(p+\frac{1}{2}\right)   

    ={\ p}^2-3p-\frac{1}{2}p-\frac{3}{2}   

    ={\ p}^2-\frac{7}{2}p-\frac{3}{2}   

         \\         

Q.5. Explain the following;

   i)  \left(4p+3\right)\left(4p+7\right)  

    ={\ 16p}^2+12p+28p+21   

    ={\ 16p}^2+40p+21   

         \\         

   ii)  \left(9c+4\right)\left(9c-2\right)  

    =\ 81c^2+36c-18c-8   

    =\ 81c^2+18c-8  

         \\         

  ii)   \left(3a-8\right)\left(3a+2\right)  

    =\ {9a}^2-24a+6a-16  

    ={\ 9a}^2-18a-16  

         \\         

  iv)  \left(5x-2\right)\left(5x-7\right)  

    =\ {25x}^2-10x-35x+14  

    ={\ 25x}^2-45x+14  

         \\         

Q.6. Find the following products;

   i)  \left(x^2+3\right)\left(x^2+6\right)  

    ={\ x}^4+{3x}^2+6x^2+18   

= x^4+9x^2+18

         \\         

  ii)  \left(y^2-1\right)\left(y^2+4\right)  

    =\ y^4-y^2+{4y}^2-4   

    ={\ y}^4+3y^2-4   

         \\         

  iii)  \left(z^2+3\right)\left(z^2-7\right)  

    ={\ z}^4+3z^2-7z^2-21   

    ={\ z}^4-4z^2-21   

         \\         

  iv)  \left(t^2-2\right)\left(t^2-5\right)  

    ={\ t}^4-2t^2-5t^2+10   

    =\ t^4-7t^2+10   

         \\         

Q.7. Find the following products;

 i)   \left(ab-2\right)\left(ab+4\right)   

    ={\ a}^2b^2-2ab++4ab-8   

    ={\ a}^2b^2+2ab-8   

         \\         

 ii)   \left(2+xy\right)\left(3-xy\right)   

    =\ {6+3xy-2xy-x}^2y^2   

    ={\ 6+xy-x}^2y^2   

         \\         

Q.8. Find the following products;

   i) \left(3x+4y\right)\left(4x+3y\right)  

    =\ 12x^2+16xy+9xy+12y^2  

    =\ 12x^2+25xy+12y^2  

         \\         

  ii)  \left(4a-5b\right)\left(3a+2b\right)  

    =\ 12a^2-15ab+8ab-10b^2  

    =\ 12a^2-7ab-10b^2  

         \\         

  iii)  \left(2y+z\right)\left(7z-3y\right)  

    =\ 14yz+7z^2-6y^2-3yz  

    =\ 7z^2+11yz-6y^2  

         \\         

 iv)   \left(2m-4n\right)\left(4m-3n\right)  

    =\ 8m^2-16mn-9mn-12n^2  

    ={\ m}^2-25mn-12n^2  

         \\         

Q.9.  Find the following products;

  i)  \left(2pq+0.1mn\right)\left(0.2pq+3mn\right)   

   =\ 0.4p^2q^2+0.02pqmn+6pqmn+0.3m^2n^2   

   =\ 0.4p^2q^2+6.02pqmn+0.3m^2n^2   

         \\         

 ii)  \left(\frac{4m}{p}-\frac{0.2n}{q}\right)\left(\frac{3m}{p}+\frac{0.5}{q}\right)   

  = \frac{12m^2}{p^2}-\frac{0.6mn}{pq}+\frac{2mn}{pq}-\frac{0.1n^2}{q^2}   

  = \ \frac{12m^2}{p^2}+\frac{1.4mn}{pq}-\frac{0.1n^2}{q^2}   

         \\         

  iii)  \left(\frac{3}{4}x-2pq\right)\left(3x-\frac{4}{5}pq\right)   

   =\ \frac{9}{4}x^2-6pqx-\frac{3}{5}pqx-\frac{8}{5}p^2q^2   

   =\ \frac{9}{4}x^2-\frac{33}{5}pqx-\frac{8}{5}p^2q^2   

         \\         

Q.10. Find the following products;

i)  \left(2a^2+3b^2\right)\left(3a^2+2b^2\right)   

  =\ 4a^4+9a^2b^2+4a^2b^2+9a^2b^2   

  =\ 4a^4+13a^2b^2+9a^2b^2   

         \\         

 ii) \left(x^2+5y^2\right)\left(y^2-2x^2\right)   

  ={\ x}^2y^2+5y^4-2x^4-10x^2y^2   

  =\ 5y^4-9x^2y^2-2x^4   

         \\         

 iii) \left(3c^2-4d^2\right)\left(4c^2-3d^2\right)   

  =\ 12c^4-16c^2d^2-9c^2d^2+12d^4   

  =\ 12c^4-25c^2d^2+12d^4   

         \\         

Advertisements